Donning the mask: the impact of Covid-19 on emotional labour performance. (9th August 2021) - Lafferty, Niamh; MacCurtain, Sarah; McNamara, Patricia Mannix
Emotional labour, the workplace management of emotions, is integral to work performance and relies on the observation and recognition of emotion in the service industry. Due to the COVID-19 pandemic, there has been a sudden global increase in the number of employees and service users required to wear face masks, resulting in a new normal for emotion expression and emotion recognition in the emotional labour performance. This paper explores emotional labour theory and proposes a theoretical consideration of the challenges and benefits this modification to the service user-employee interaction may have. Suggested challenges include changes to the service user-employee relationship due to impaired communication and increased customer anxiety and frustrations. Organisational responses are discussed in relation to training and cross-industrial sharing of knowledge. Finally, opportunities for organisational research are discussed alongside suggestions for future research.